PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. RIAU POWER PEKANBARU - Nurhayana, Nurhayana (Eko dan Bisnis: Riau Economic and Business Review, 2019)
The purpose of this study was to determine the effect of motivation and job satisfaction on the performance of employees of PT. Riau Power Pekanbaru. The population of data collected in the study were all 34 employees. The sampling technique used is the census technique, which is used when the population is all sampled, to determine the results using SPSS as an analysis tool. The results of the study stated that motivation and job satisfaction partially and simultaneously had a positive and significant effect on performance, and the coefficient of determination of 66% and 34% was influenced by other variables not examined in this study